Bragg‐edge attenuation spectra at voxel level from 4D wavelength‐resolved neutron tomography. Issue 1 (30th January 2020) - Carminati, Chiara; Strobl, Markus; Minniti, Triestino; Boillat, Pierre; Hovind, Jan; Morgano, Manuel; Holm Rod, Thomas; Polatidis, Efthymios; Valsecchi, Jacopo; Mannes, David; Kockelmann, Winfried; Kaestner, Anders
Abstract : A wavelength‐resolved neutron tomography study is performed on a reference sample made of several polycrystalline materials, namely nickel, iron, titanium, lead, copper and aluminium. Wavelength‐resolved total cross sections for each material and for each voxel in the reconstructed volume of the sample were retrieved. Abstract : 4D wavelength‐resolved neutron tomography of a reference sample made of several polycrystalline materials, namely nickel, iron, titanium, lead, copper and aluminium, is presented. Data were acquired using the time‐of‐flight transmission imaging method at the IMAT beamline at the ISIS pulsed neutron source. Wavelength‐dispersive tomography reconstruction was computed using filtered back projection, allowing wavelength‐resolved total‐cross‐section retrieval for each voxel in the reconstructed volume of the sample. The need for background correction to enable quantitative results and analysis is discussed, and the achieved 3D spatial resolution with respect to the obtained Bragg‐edge pattern quality is investigated.